دراسة بعض خصائص بلازما نواتج الاحتراقً (Latakia University Journal -Basic Sciences Series, 2018)
نتيجة لأهمية بلازما نواتج الاحتراق ودخولها في الصناعة بمساعدة المولدات الهيدروديناميكية المغناطيسية  ،(MHD)درست في النصف الثاني من القرن العشرين خواص ومكونات البلازما بشكل ملحوظ ولكن نتيجة لحداثة دراسة بلازما نواتج الاحتراق ما زالت هناك جوانب تحتاج إلى إلقاء الضوء عليها وخاصة الجوانب المتعلقة بما يجري من عمليات وتفاعلات داخلها، من هنا شملت دراستنا التالي: 1- تحديد شروط التوازن الكيميائي من خلال معالجة قانون الكتلة الفعالة. 2- دراسة طاقة الحالة الأساسية وطاقة التفكك إحصائياً لبلازما نواتج الاحتراق والحسابات الترموديناميكية لبلازما نواتج الاحتراق. بتحديد شروط التوازن الكيميائي تم التوصل إلى قانون الكتلة الفعالة والذي يوضح العلاقة بين تركيز الكتلة والمجموع الإحصائي، ومنه عين ثابت توازن التفاعل الكيميائي، وبناءً عليه عين المجموع الإحصائي الانسحابي، والوزن الإحصائي للسوية وحددت مساهمة الحركة الاهتزازية في المجموع الإحصائي وتم حساب طاقة الحالة الأساسية وطاقة التفكك. Due to the importance of the plasma of combustion products and its application in industry with the aid of the magnetic hydrodynamic generators (MHD). Its properties and its constituents were studied noticeably in the late 20-th century, but since these studies were new, they did not include all the points related to the processes and interactions which take place within it. Therefor, our study was focussed on two directions: • Determination of chemical balance conditions by reforming the active masses law.• Studying the energy of the main state and decomposition energy statisticaly. By determining the conditions of chemical balance, the law of active masses was found. This law explains the relation between the mass concentration and statistical sum, and from it the balance constant of chemical interaction was determined, moreover, based on it, the transformed statistical sum and the statistical weight level were also determined. The participation of the vibration movement in the statistical sum was determined. Calculation of the energy of the main state and decomposition energy was also performed.